Colour atlas of ophthalmology - Lim, Arthur Siew Ming (World Scientific, 2001)
From the Manhattan Eye, Ear, and Throat Hospital, one of the most prestigious institutions in the U.S. comes the Color Atlas of Ophthalmology, a convenient, pocket-sized tool to help physicians make quick and accurate diagnoses of commonly encountered disorders. For each condition, the book presents a high-quality clinical photograph accompanied by a concise review of symptoms, associated findings, differential diagnosis, work-up, and treatment